Early Life Stress Restricts Translational Reactivity in CA3 Neurons Associated With Altered Stress Responses in Adulthood - Marrocco, Jordan; Gray, Jason D.; Kogan, Joshua F.; Einhorn, Nathan R.; O’Cinneide, Emma M.; Rubin, Todd G.; Carroll, Thomas S.; Schmidt, Eric F.; McEwen, Bruce S. (Frontiers in Behavioral Neuroscience, 2019)
Early life experiences program brain structure and function and contribute to behavioral endophenotypes in adulthood. Epigenetic control of gene expression by those experiences affect discrete brain regions involved in mood, cognitive function and regulation of hypothalamic-pituitary-adrenal (HPA) axis. In rodents, acute restraint stress increases the expression of the repressive histone H3 lysine 9 tri-methylation (H3K9me3) in hippocampal fields, including the CA3 pyramidal neurons. These cells are crucially involved in cognitive function and mood regulation as well as activation of glucocorticoid (CORT) secretion. CA3 neurons also exhibit structural and functional changes after early-life stress as well as after chronic stress in adulthood. Using a protocol of chronic early-life stress (ELS) induced by limited bedding and nesting material followed by acute-swim stress (AS) in adulthood, we show that mice with a history of ELS display a blunted CORT response to AS, despite exhibiting activation of immediate early genes after stress similar to that found in control mice. We find that ELS induced persistent increased expression of the repressive H3K9me3 histone mark in CA3 subfield at baseline that was subsequently decreased following AS. In contrast, AS induced a transient increase of this mark in control mice. Using translating ribosome affinity purification (TRAP) method to isolate CA3 translating mRNAs, we found genes of the epigenetic gene family, GABA/glutamate family, and glucocorticoid receptors binding genes that were decreased transiently in control mice by AS and that showed a persistent reduction in ELS mice. In most cases, AS in ELS mice did not induce gene expression changes. A stringent filtering of genes affected by AS in control and ELS mice revealed a noteworthy decrease in gene expression change in ELS mice compared to control. Only eighteen genes were selectively regulated by AS in ELS mice and encompassed pathways such as circadian rhythm, inflammatory response, opioid receptors, and more genes included in the glucocorticoid receptor binding family. Thus, ELS programs restricted translational response to stress in stress-sensitive CA3 neurons leading to persistent changes in gene expression that mimic the transient effects of AS in control mice, while leaving in operation the immediate early gene response to AS.